Meiosis in elephant grass (Pennisetum purpureum), pearl millet (Pennisetum glaucum) (Poaceae, Poales) and their interspecific hybrids - Vânia Helena Techio (Genetics and Molecular Biology, 2006)
The cultivated and sexually compatible species Pennisetum purpureum (elephant grass, 2n = 4x = 28) and Pennisetum glaucum (pearl millet, 2n = 2x = 14) can undergo hybridization which favors the amplification of their genetic background and the introgression of favorable alleles into breeding programs. The main problem with interspecific hybrids of these species is infertility due to triploidy (2n = 3x = 21). This study describes meiosis in elephant grass x pearl millet hybrids and their progenitors. Panicles were prepared according to the conventional protocol for meiotic studies and Alexander’s stain was used for assessing pollen viability. Pearl millet accessions presented regular meiosis with seven bivalents and high pollen viability. For elephant grass, 14 bivalents in diakinesis and metaphase I were observed. The BAG 63 elephant grass accession, derived from tissue culture, presented a high frequency of meiotic abnormalities. The three hybrid accessions presented a high frequency of abnormalities characterized by irregular chromosomal segregation which resulted in the formation of sterile pollen.